Perlindungan Hukum Terhadap Hak Pekerja Akibat Pemutusan Hubungan Kerja (PHK) Sepihak pada Perusahaan Alihdaya (Outsourcing) di Dinas Tenaga Kerja, Koperasi, dan UKM Kota Gorontaloa - Rahmat Ramdhan Arsyad (Perspektif Administrasi Publik dan hukum, 2025)
This study aims to analyze the legal protection of workers' rights due to unilateral termination of employment (PHK) in outsourcing companies in Gorontalo City. The focus of the study covers two main aspects, namely the form of fulfillment of workers' rights affected by layoffs and the inhibiting factors of the Gorontalo City Manpower, Cooperatives, and SMEs Office in providing legal protection. The research method used is an empirical legal approach with data collection through interviews, document studies, and observations. The results of the study indicate that the fulfillment of workers' rights includes severance pay, long-service bonus money, and replacement money in accordance with applicable regulations. In addition, the relevant agencies play a role in providing mediation services and facilitating dispute resolution. However, the implementation of this legal protection faces various obstacles, such as low legal awareness of workers, limited human resources and budget in the Manpower Office, and weak supervision of outsourcing companies. This study emphasizes the need to strengthen labor regulations and increase the effectiveness of supervision to ensure optimal protection of workers' rights. The results of the study are expected to be a reference for policy makers and related parties in improving the legal protection mechanism for workers affected by layoffs.